Prebiotics Inulin Metabolism by Lactic Acid Bacteria From Young Rabbits - Zhu, Yuan-ting; Yue, Shuang-ming; Li, Rui-tong; Qiu, Shi-xiu; Xu, Zhen-Ying; Wu, Yi; Yao, Jin; Zuo, Yong; Li, Ke-juan; Li, Yang (Frontiers in Veterinary Science, 2021)
Inulin as commercial prebiotics could selectively promote the growth of gut beneficial microbes such as lactic acid bacteria (LAB), while whether LAB in rabbit gut possess the capability to metabolize and utilize inulin is little known. Therefore, this study recovered ninety-four LAB strains from neonate rabbits and found that only 29% (28/94) could metabolize inulin with both species- and strain-specificity. The most vigorous inulin-degrading strain Lacticaseibacillus paracasei YT170 could efficiently utilize both short-chain and long-chain components through thin-layer chromatography analysis, and from genomic analysis, a predicted fosRABCDXE operon encoding putative cell wall-anchored fructan β-fructosidase and five fructose-transporting proteins and a pts1BCA operon encoding putative β-fructofuranosidase and sucrose-specific IIBCA components linked to long-chain and short-chain inulin utilization respectively. This study provides a mechanistic rationale for effect of inulin administration on rabbits and lays a foundation for synbiotic applications aimed at modulating intestinal microbiota of young rabbits.